2019
DOI: 10.1111/asj.13161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on growth performance, rectal temperature and serum parameters of yellow‐feather broilers under heat stress

Abstract: This study investigated the effect of dietary resveratrol supplementation on growth performance, rectal temperature, and serum parameters of yellow‐feather broilers under heat stress. A total of 480 yellow‐feather broilers (28‐day‐old) were randomly allotted to five groups with six replicates. A thermoneutral group (TN) (24 ± 2°C) received a basal diet and another four heat‐stressed groups (37 ± 2°C for 8 hr/day and 24 ± 2°C for the remaining time) were fed the basal diet or basal diet with 200, 350, and 500 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 38 publications
12
32
1
Order By: Relevance
“…In addition, peripheral vasodilation (decreased peripheral vascular resistance) proceeds this temporary hyperthyroidism and leads to elevated HR. Hyperthermia in animals is known to raise the activity of circulating free radicals and concurrently results in compromised TAO [29]. The alleviation of hyperthermia by KI in the current experiment accompanied by resistance to TAO decline (as compared to the CN group) is consistent with our previous work [30] showing an improved antioxidant status in rats when hyperthermia (elicited by similar HS conditions) was mitigated.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, peripheral vasodilation (decreased peripheral vascular resistance) proceeds this temporary hyperthyroidism and leads to elevated HR. Hyperthermia in animals is known to raise the activity of circulating free radicals and concurrently results in compromised TAO [29]. The alleviation of hyperthermia by KI in the current experiment accompanied by resistance to TAO decline (as compared to the CN group) is consistent with our previous work [30] showing an improved antioxidant status in rats when hyperthermia (elicited by similar HS conditions) was mitigated.…”
Section: Discussionsupporting
confidence: 92%
“…This research clearly confirms that GABA can reduce the negative impact on blood biochemical indices caused by a high temperature. The possible mechanism might be that additive suppressed the expression of HSPs, which improves insulin sensitivity, leading to glycolysis and fat synthesis, and regulation of serum GLU, T-CHO, and TG contents under heat stress (He et al 2019). However, no significant differences appeared in the levels of TG, which was not the same as previous research (Zhang et al 2012).…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies have shown that supplementation of resveratrol (400 mg/kg of feed) enhanced the antioxidant capacity in the broilers during heat stress [ 106 ]. Supplementation of resveratrol at 300 or 500 mg/kg of feed improved the average daily gain, decreased the rectal temperature, lowered the level of corticosterone, adrenocorticotropin hormone, cholesterol, and MDA in yellow-feather broilers under heat stress [ 107 ]. Additionally, in the same study, resveratrol also increased the level of triiodothyronine, glutathione, total superoxide dismutase, catalase, and glutathione peroxidase during heat stress [ 107 ].…”
Section: Potential Strategies To Mitigate Heat Stress In Poultrymentioning
confidence: 99%
“…Supplementation of resveratrol at 300 or 500 mg/kg of feed improved the average daily gain, decreased the rectal temperature, lowered the level of corticosterone, adrenocorticotropin hormone, cholesterol, and MDA in yellow-feather broilers under heat stress [ 107 ]. Additionally, in the same study, resveratrol also increased the level of triiodothyronine, glutathione, total superoxide dismutase, catalase, and glutathione peroxidase during heat stress [ 107 ]. Resveratrol also improved different gut health parameters such as microbial profile, villus-crypt structure, and expression of the tight junction and adherence junction related genes in the heat-stressed broilers [ 108 ] Interestingly, resveratrol improved meat quality in the heat-stressed broilers by increasing the muscle total antioxidant capacity (T-AOC) and activity of antioxidant enzymes (catalase, GSH-Px) [ 109 ].…”
Section: Potential Strategies To Mitigate Heat Stress In Poultrymentioning
confidence: 99%